Six tips for moving web services from the lab into action flexibility, security and manageability are the watchwords. - Kaufman, Joelle Gropper (SOA webservices journal.)
It's relatively easy to built custom Web services. Customers are finding that it's much more difficult, however, to successfully secure and scale them in production. Six tips from Canada's largest loyalty reward program provide, a global financial services company and reactivity, Inc. can help you simplify Web services deployment.